2002
DOI: 10.1354/vp.39-2-240
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of a New Histologic Grading System for Canine Osteosarcoma

Abstract: Histologic grade is an important determinant in clinical outcome of human osteosarcoma (OS). In this study, the histologic characteristics of primary and metastatic canine OS were evaluated using a new classification system. Histologic characteristics were classified in 166 primary and 34 metastatic canine OS. Prognostic variables for clinical outcome were determined using multivariate analysis. Most OS were histologically characterized by severe to extreme cellular pleomorphism, a variable number of mitoses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
168
3
11

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(188 citation statements)
references
References 30 publications
6
168
3
11
Order By: Relevance
“…Data from 20 studies were included in this IPDMA, of which 11 studies were previously published (Kurzman et al, 1995;Berg et al, 1997;Kirpensteijn et al, 2002;Vail et al, 2002;Morello et al, 2003;Moore et al, 2007;Bacon et al, 2008;Kow et al, 2008;Phillips et al, 2009;Sottnik et al, 2010). 19 studies reported solely on large breed dogs, while the unpublished study of Dr. Amsellem included 36 small breed canines.…”
Section: Resultsmentioning
confidence: 99%
“…Data from 20 studies were included in this IPDMA, of which 11 studies were previously published (Kurzman et al, 1995;Berg et al, 1997;Kirpensteijn et al, 2002;Vail et al, 2002;Morello et al, 2003;Moore et al, 2007;Bacon et al, 2008;Kow et al, 2008;Phillips et al, 2009;Sottnik et al, 2010). 19 studies reported solely on large breed dogs, while the unpublished study of Dr. Amsellem included 36 small breed canines.…”
Section: Resultsmentioning
confidence: 99%
“…9,17,20,22 Mesenchymal tissue is known to possess high differentiation potential, and this explains the multipotential characteristics of the neoplasm in this case. In humans, although osseous neoplasms containing malignant chondroblastic or fibroblastic populations have been associated with a better prognosis, 3,12,20,23 there is still much debate in human and veterinary medicine whether histologic features of these neoplasms truly correlate with their prognosis.…”
mentioning
confidence: 77%
“…17 Metastatic components may impart a differing histologic appearance in cell type and matrix formation than the primary tumor. 9,17 Secondary or metastatic tumors may affect bone either by direct extension or by hematogenous spread. We present a case of osteosarcoma apparently arising synchronously in multiple long bones in a 1.5-year-old dog.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding highlights the importance of necropsy as a post mortem diagnostic method, because it allowed macroscopic evaluation of the tumor, as well as collection of samples for microscopic evaluation. Histopathological analysis is the most indicated test for the diagnosis of osteosarcoma (KIRPENSTEIJN et al, 2002;LOUKOPOULOS;ROBINSON, 2007) and allows classification of the tumor based on formation of osteoid matrix into osteoblastic, fibroblastic, chondroblastic, and telangiectasic subtypes (KIRPENSTEIJN et al, 2002;LOUKOPOULOS;ROBINSON, 2007).…”
Section: Case Reportmentioning
confidence: 99%